TO THE QUESTION OF THE DIFFERENCE OF PROFESSIONAL AND CORPORATE ETHICS - Muhiddinovna, Toshpolatova Shirin (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses various aspects of professional and corporate ethics. Analysis of corporate misconduct important issues addressed in the literature. Discussion of the relationship of authors to corporate ethics.